2011
DOI: 10.1002/ccd.22867
|View full text |Cite
|
Sign up to set email alerts
|

Radiation safety program for the cardiac catheterization laboratory

Abstract: The Society of Cardiovascular Angiography and Interventions present a practical approach to assist cardiac catheterization laboratories in establishing a radiation safety program. The importance of this program is emphasized by the appropriate concerns for the increasing use of ionizing radiation in medical imaging, and its potential adverse effects. An overview of the assessment of radiation dose is provided with a review of basic terminology for dose management. The components of a radiation safety program i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
201
0
11

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 275 publications
(216 citation statements)
references
References 62 publications
1
201
0
11
Order By: Relevance
“…During CA, real‐time monitoring of radiation doses and exposure factors such as tube potential (kV), tube current (mA), fluoroscopy time, and number of cine acquisition for each angiographic projection were elicited by personnel involved in data collection. Reference air‐kerma (Ka,r) values which serves as a dose indicator for deterministic effects were estimated at the interventional reference point (IRP) (18) . In order to estimate gender‐based radiation risks, effective dose (ED) and organ doses (breasts, heart, lungs) and radiation exposure‐induced cancer death (REID) associated to cardiovascular imaging were calculated using PC‐based Monte Carlo simulation software (PCXMC) developed by STUK (Radiation and Nuclear Safety Authority, Helsinki, Finland) (19) .…”
Section: Methodsmentioning
confidence: 99%
“…During CA, real‐time monitoring of radiation doses and exposure factors such as tube potential (kV), tube current (mA), fluoroscopy time, and number of cine acquisition for each angiographic projection were elicited by personnel involved in data collection. Reference air‐kerma (Ka,r) values which serves as a dose indicator for deterministic effects were estimated at the interventional reference point (IRP) (18) . In order to estimate gender‐based radiation risks, effective dose (ED) and organ doses (breasts, heart, lungs) and radiation exposure‐induced cancer death (REID) associated to cardiovascular imaging were calculated using PC‐based Monte Carlo simulation software (PCXMC) developed by STUK (Radiation and Nuclear Safety Authority, Helsinki, Finland) (19) .…”
Section: Methodsmentioning
confidence: 99%
“…Radiation reduction methods are outdated, and new proposals have been presented. [14][15][16][17][18] It has been stipulated that ionising radiation exposure should be as low as possible when it is inevitable. The "as low as reasonably achievable" (ALARA) principle, 19,20 established in 1977, essentially states that radiation exposure should be kept as low as reasonably achievable.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, medical societies are encouraging more training programs and education measures to reduce the biological risks. 1,16,17 The area exposed to biological radiation effects and the potential stochastic risks of neoplasia are as important as the total radiation dose. The present study demonstrated that there is a strong relation between the total received dose and the irradiated area, regardless of the patient's weight.…”
Section: Discussionmentioning
confidence: 99%
“…Interventionists should strive to minimize radiation doses during PCI [111][112][113][114] as outlined in Table IV. A radiation safety program that uses a qualified physicist, dosimetry monitoring, shielding, and training is essential [113].…”
Section: Managing Radiation Dosesmentioning
confidence: 99%
“…If K a,r > 10 Gy is delivered during a procedure, a qualified physicist should calculate the actual peak skin dose and assess potential tissue injury (Table IV). Appropriate steps for patient follow-up based on radiation dose should be followed [113].…”
Section: Managing Radiation Dosesmentioning
confidence: 99%